Internet Of Things Based Home Electrical Control Device Using Google Assistant - Agusli, Rachmat; Tullah, Rahmat; Akbar Jurfri, Ali (STMIK Bina Sarana Global, 2021)
The increasing use of the internet has resulted in innovations in control systems. Internet of Things or IoT is an innovation where several electronic devices can be controlled remotely by utilizing the internet to obtain a more efficient and time-saving control system. This research uses IoT to control several electronic devices that are usually used in homes, such as lights, fans, and many more. The system built based on the Internet of Things uses Google Assistant or voice by utilizing the NodeMCU device as a control system. With the construction of this application, it is hoped that it can make it easier for people to turn on and turn off lights remotely. Users are only asked to press the voice commad or button on the Android application that was built to carry out the command to turn on and turn off the lights by using an internet connection. Based on the test results, the system can work properly to turn the lights on and off in a long distance.